2020
DOI: 10.1126/sciadv.aba8555
|View full text |Cite
|
Sign up to set email alerts
|

Landscapes of bacterial and metabolic signatures and their interaction in major depressive disorders

Abstract: Gut microbiome disturbances have been implicated in major depressive disorder (MDD). However, little is known about how the gut virome, microbiome, and fecal metabolome change, and how they interact in MDD. Here, using whole-genome shotgun metagenomic and untargeted metabolomic methods, we identified 3 bacteriophages, 47 bacterial species, and 50 fecal metabolites showing notable differences in abundance between MDD patients and healthy controls (HCs). Patients with MDD were mainly characterized by increased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
185
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(201 citation statements)
references
References 42 publications
15
185
1
Order By: Relevance
“…In the DL macaques, the altered phages mainly parasitize Proteobacteria and Firmicutes bacteria. Interestingly, we recently found similar viral disturbances in MDD patients [36], in which the altered gut viruses were mainly bacteriophages too. The MDD patients had increased Siphoviridae but decreased Podoviridae viral family populations, which aligns with our findings in the DL macaques described herein.…”
Section: Discussionmentioning
confidence: 54%
“…In the DL macaques, the altered phages mainly parasitize Proteobacteria and Firmicutes bacteria. Interestingly, we recently found similar viral disturbances in MDD patients [36], in which the altered gut viruses were mainly bacteriophages too. The MDD patients had increased Siphoviridae but decreased Podoviridae viral family populations, which aligns with our findings in the DL macaques described herein.…”
Section: Discussionmentioning
confidence: 54%
“…Bacteroidales is the most common microbial category in the human gut. It takes signi cant roles in metabolic pathways and immune system (47). Previous studies reported that acquired inter bacterial defense gene clusters in Bacteroidales species reside in the human gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the recent progress in the understanding of phages and in the methods of their genetic modification may soon make construction of engineered phages a routine procedure rather than a tedious scientific undertaking. Additionally, the new discoveries concerning the interaction of phages with bacteria inside the human body and the effect of phages on human health via their influence on the microbiome open up new possibilities of therapeutic application of modified phages not only to treat infections with bacterial pathogens, but also to improve the conditions of patients suffering from diverse disorders related to a dysfunctional microbiome, by in situ microbiome engineering [ 69 , 71 73 , 156 159 ].…”
Section: Engineered Phages As Future Therapeutic Options: Rationale and Perspectivesmentioning
confidence: 99%